2004
DOI: 10.3989/scimar.2004.68n4537
|View full text |Cite
|
Sign up to set email alerts
|

Composition and distribution of benthic molluscs on intertidal flats of Paranaguá Bay (Paraná, Brazil)

Abstract: SUMMARY: Mollusc species composition, abundance and spatial distribution were analysed from April 1996 to October 1997 on two tidal flats in Paranaguá Bay (SE Brazil) at the entrance (St. I) (Lat. 25º32'S) and in the intermediate sector (St. II) (Lat. 25º30'S) of the estuary. At St. I, with the highest and least variable salinity, species richness (R = 40) and diversity (H´ = 1; D S = 0.85) were higher than at St. II (R = 22 and H´ = 0.54; D S = 0.57). The tropical clam Anomalocardia brasiliana was the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
(15 reference statements)
3
20
0
2
Order By: Relevance
“…Therefore, although this gastropod can also inhabit estuarine sandy beaches (Petracco, personal observation), its occurrence seems to be more restricted than O. minuta. In fact, besides the frequent occurrence in sheltered, and in reflective and dissipative exposed sandy beaches (Denadai et al 2005;Petracco et al 2014;Rocha-Barreira et al 2005), O. minuta is also frequently recorded in tidal flats and estuaries (e.g., Boehs et al 2004;Rolemberg et al 2008).…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, although this gastropod can also inhabit estuarine sandy beaches (Petracco, personal observation), its occurrence seems to be more restricted than O. minuta. In fact, besides the frequent occurrence in sheltered, and in reflective and dissipative exposed sandy beaches (Denadai et al 2005;Petracco et al 2014;Rocha-Barreira et al 2005), O. minuta is also frequently recorded in tidal flats and estuaries (e.g., Boehs et al 2004;Rolemberg et al 2008).…”
Section: Resultsmentioning
confidence: 96%
“…A similar pattern was found by (Dankers & Beukema, 1981) in the Wadden Sea, but Edgar and Barrett (2002) found that in Tasmanian estuaries the number of species and abundance continued to increase as they moved down shore to 0.7 m below low water mark. Honkoop et al (2006) found greater numbers of individuals and species at lower tidal levels in northwestern Australia, and Boehs et al (2004) found that molluscs decreased in abundance and diversity at higher tidal levels, i.e. between mid-and high tide.…”
Section: Spatial Variationmentioning
confidence: 97%
“…Many studies have investigated the distribution (Chainho et al, 2006;Rodrigues et al, 2006), abundance Dittman, 2002b), diversity (Boehs et al, 2004) and biomass (Masero et al, 1999;Silva et al, 2006) of invertebrates on intertidal flats. There have also been many studies that examine the effect of environmental variables on invertebrate abundance and community composition (Anderson, 1972;Castel et al, 1989;Edgar & Barrett, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…(Rios, 1994). É uma das espécies de molu sco mais frequentes nas praias abrigadas do Canal de São Sebastião, litoral norte do Estado de São Paulo (Denadai et al 2005), e uma das espécies mais abundantes na praia de Barequeçaba (Shimizu, 1991) (Severeyn et al 2003;Boehs et al 2004), a sua distribuição espacial (Shimizu, 1991;Viana et al 2005;) a 9 mm 1m 1,5m…”
Section: Introdução Geralunclassified
“…No entanto, a exemplo de Barequeçaba, a maioria dos estudos da macrofauna de praias arenosas são desenvolvidos com espécies exclusivas da porção emersa da praia, do pós-praia ou migradores mareais (ver Severeyn et al 2003;Arruda e Amaral, 2003;Boehs et al 2004;Denadai et al 2005;Camargo, 2012 Possui aproximadamente 1200 metros de extensão, delimitada por dois costões rochosos, perfil suave (~0,78°) e sedimento composto por areia fina e muito fina, com baixo conteúdo de matéria orgânica (~0,75%) (Nucci et al 2001;Denadai et al 2005, Tominaga et al 2006. Barequeçaba recebe constantemente descargas de água doce, provenientes de um riacho permanente localizado na porção Leste da praia e de um número variado de pequenos cursos da água temporários (Shimizu, 1991).…”
Section: Introdução Geralunclassified